Through scaffolding and catalytic actions nucleoside diphosphate kinase B differentially regulates basal and β-adrenoceptor-stimulated cAMP synthesis - Hippe, Hans-Jörg; Abu-Taha, Issam H.; Wolf, Nadine M.; Katus, Hugo; Wieland, Thomas (Cellular signalling, 2011)
β-adrenoceptors (βAR) play a central role in the regulation of cAMP synthesis and cardiac contractility. Nucleoside diphosphate kinase B (NDPK B) regulates cAMP signalling by complex formation with Gβγ dimers thereby activating and stabilizing heterotrimeric Gs proteins, key transducer of βAR signals into the cell. Here, we explored the requirement of NDPK B for basal and βAR-stimulated cAMP synthesis and analysed the underlying mechanisms by comparing wild-type NDPK B (WT) and its catalytically inactive H118N mutant. Stable overexpression of both WT- and H118N-NDPK B in cardiomyocyte derived H10 cells increased the plasma membrane content of Gs and caveolin-1 and thus enhanced the isoproterenol (ISO)-stimulated cAMP-synthesis by about 2-fold. Conversely, the loss of NDPK B in embryonic fibroblasts from NDPK A/B-depleted mice was associated with a severe reduction in membranous Gs protein and carveolin-1 content causing a marked decrease in basal and ISO-induced cAMP formation. Re-expression of NDPK B, but not of NDPK A, was able to rescue this phenotype. Both, re-expression of WT- and H118N-NDPK B induced the re-appearance of Gs and caveolin-1 at the plasma membrane to a similar extent. Accordingly, WT- and H118N-NDPK B similarly enhanced ISO-induced cAMP formation. In contrast, the catalytically inactive H118N-NDPK B was less potent and less effective in rescuing basal cAMP production. Identical results were obtained in neonatal rat cardiac myocytes after siRNA-induced knockdown and adenoviral re-expression of NDPK B. Our data reveal that NDPK B regulates Gs function by two different mechanisms. The complex formation of NDPK B with Gs is required for the stabilization of the G protein content at the plasma membrane. In addition, the NDPK B-dependent phosphotransfer reaction, which requires the catalytic activity, specifically allows a receptor-independent, basal Gs activation.
Gesehen am 13.09.2022
Available online 25 November 2010